The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/bf03395507
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Limits of the Matching Concept in Cebus Apella: A Matter of Experimental Control?

Abstract: The capacity to exhibit generalized sameness-difference judgments is a hallmark of cognition that is regularly exhibited by humans. As yet, that capacity has not been well documented in New World monkeys such as the capuchin (Cebus apel/a). This article presents data obtained with 6 capuchi n monkeys with a variety of procedures that might lead to gEmeralized identity matching-to-sample (MTS) in this species, reporting part of a research program conducted to evaluate methods for assessing the species' relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
0
25
0
4
Order By: Relevance
“…The program includes not only nonhuman primates (e.g., Galvão et al, 2005) but also preverbal children (Gil & Oliveira, under review) and nonverbal children with autism spectrum disorders. The second study reported here addressed the last of these populations.…”
mentioning
confidence: 99%
“…The program includes not only nonhuman primates (e.g., Galvão et al, 2005) but also preverbal children (Gil & Oliveira, under review) and nonverbal children with autism spectrum disorders. The second study reported here addressed the last of these populations.…”
mentioning
confidence: 99%
“…Emergent conditional relations are generally tested in the absence of programmed reinforcement (i.e., extinction) to ensure that performance is not explicitly trained during the test. However, the absence of programmed reinforcement may be a possible cause of digressions in stimulus control during the tests (Dube & McIlvane, 1996;Galvão et al, 1992) and may establish a discriminated repertoire that produces negative results during testing (Brino et al, 2009;Galvão et al, 2005). Extinction can also lead to the occurrence of resurgent behaviors (Epstein, 1983(Epstein, , 1985Villas-Bôas, Murayama, & Tomanari, 2005;Wilson & Hayes, 1996), aggression (Azrin, Hutchinson, & Hake, 1966;Keller & Schoenfeld, 1950;Skinner, 1938), and an increase in behavioral variability (Antonitis, 1951;Lerman & Iwata, 1996).…”
Section: Assessing Symmetry In Capuchin Monkeysmentioning
confidence: 99%
“…As mentioned above, some studies reported positive results of symmetry assessment by controlling the stimulus location during training and restricting the stimuli to only one possible location during testing using a successive Go/No-Go procedure (e.g., Frank, 2007;Frank & Wasserman, 2005;Urcuioli, 2008;Vasconcelos & Urcuioli, 2011). The present study implemented such stimulus-location control using multiple sample and comparison locations in a 3 x 3 matrix (as used by Brino et al, 2009;Barros et al, 2002;Barros, Galvão, & McIlvane, 2002;Galvão et al, 2005).…”
Section: Assessing Symmetry In Capuchin Monkeysmentioning
confidence: 99%
“…Schusterman and Kastak (1993) and Kastak, Schusterman, and Kastak (2001) studied sea lions and reported emergent symmetric, transitive, and equivalence relations (Sidman, & Tailby, 1982). However, the necessary conditions to obtain the emergence of derived relations in nonhumans have not been established (Sidman, 1994; Galvão et al, 2005). Knowledge of the variables responsible for intra- and inter-subject baseline performance variability has been suggested to be a possible source for predicting derived emergent relations (Galvão et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the necessary conditions to obtain the emergence of derived relations in nonhumans have not been established (Sidman, 1994; Galvão et al, 2005). Knowledge of the variables responsible for intra- and inter-subject baseline performance variability has been suggested to be a possible source for predicting derived emergent relations (Galvão et al, 2005). Extant reports of derived repertoires involve special sets of conditions with various species, but no analysis of the variables that could explain both successes and failures has been performed.…”
Section: Introductionmentioning
confidence: 99%